Fotografias e histórias - Koutsoukos, Sandra (Afro-Ásia, 2020)
Resenha de: FOX-AMATO, Matthew. Exposing Slavery. Photography, Human Bondage, and the Birth of Modern Visual Politics in America. Nova York: Oxford University Press, 2019. 343p.